2016
DOI: 10.1159/000446244
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of ADAMTS Proteases and Their Substrates in Epithelial Ovarian Cancer

Abstract: Background: ADAMTS are metalloproteases with disintegrin and thrombospondin motifs. They are secreted proteases playing a role in biological processes such as inflammation, angiogenesis, and urogenital development. ADAMTS have specific substrates, such as the proteoglycans (PG) versican, aggrecan, and brevican. Despite data indicating a role of ADAMTS in tumor invasion and metastases, effects played by these molecules in cancer progression are still controversial. In ovarian cancer, the importance of ADAMTS ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 62 publications
(46 reference statements)
1
15
0
1
Order By: Relevance
“…Combined with the clinical follow-ups, we identified the overexpressed ADAMTS4 as a crucial factor in CRC progression. Consistently, the overexpressed prolife of ADAMTS4 has been reported in several cancers including glioblastoma [25], head and neck cancer [26], melanoma [27], and epithelial ovarian cancer [12]. By immunochemical analysis of a CRC tissue microarray, we confirmed that ADAMTS4 expression was elevated in CRC tissues compared to normal tissues and predicted a poor prognosis in CRC.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Combined with the clinical follow-ups, we identified the overexpressed ADAMTS4 as a crucial factor in CRC progression. Consistently, the overexpressed prolife of ADAMTS4 has been reported in several cancers including glioblastoma [25], head and neck cancer [26], melanoma [27], and epithelial ovarian cancer [12]. By immunochemical analysis of a CRC tissue microarray, we confirmed that ADAMTS4 expression was elevated in CRC tissues compared to normal tissues and predicted a poor prognosis in CRC.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, by loss-of-function study, genetic silencing of ADAMTS4 showed no obvious implications on cell proliferation and invasive capacity of CRC cells with high ADAMTS4 expression, but remarkably suppressed tumor in vivo, indicating the regulatory roles of ADAMTS4 are largely dependent on ECM. Extensive remodeling of the normal ECM in cancers can progress via the degradation of preexisting ECM molecules, such as aggrecan, brevican, and versican [12]. Alterations in the extracellular environment are critical for tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cleavage of proteoglycans like aggrecan and versican by a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) in epithelial ovarian cancer has been demonstrated and is considered of prognostic value (75).…”
Section: Proteoglycansmentioning
confidence: 99%
“…In addition, TFPI-2 is a binding partner and substrate of ADAMTS1 [147]. ADAMTSs were found to be upregulated in EOC tissues [148]. Thus, it is feasible that ADAMTS as well as MMPs influence coagulation factor-driven inflammatory responses in EOC tissue.…”
Section: Potential Tf-fviia-driven Inflammatory Responses Within Hmentioning
confidence: 99%